HUBUNGAN PENGETAHUAN GIZI SEIMBANG, FREKUENSI KONSUMSI JUNK FOOD DAN PEMANTAUAN BERAT BADAN DENGAN IMT/U PADA REMAJA PUTRI DI FTC CHEERLEADERS - Ruth Fransisca Hutagalung (2021)
Adolescence is an important period of growth in determining the life experienced by every living being. The majority of adolescents are prone to nutritional problems due to the need for nutrients that continue to increase along with growth. Indicators of measurement of a person's nutritional status are related to Body Mass Index (BMI) and Age (U) in determining the category of nutritional status. Some indirect causes of nutritional status imbalances are based on balanced nutrition knowledge, frequency of consumption and periodic weight monitoring. The purpose of this study was to find out the relationship of balanced nutrition knowledge, frequency of junk food consumption and weight monitoring with BMI/U in young women in FTC Cheerleaders. This research method uses quantitative approach with crosssectional design. This study sampled 60 respondents using simple random sampling techniques. Data analysis in this study used chi-square statistical test. The results of bivariate data analysis showed that there was relationship between balanced nutrition knowledge (p=0,024) with BMI/U and no relationship frequency of junk food consumption (p=0.664) and weight monitoring (p=0.392) with BMI/U in young women.